2013
DOI: 10.1039/c2dt32347h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cyclopropanation of olefins catalysed by Cu(i) complexes of chiral pyridine-containing macrocyclic ligands (Pc-L*)

Abstract: The synthesis and characterisation of copper(I) complexes of chiral pyridine-containing macrocyclic ligands (Pc-L*) and their use as catalysts in asymmetric cyclopropanation reactions are reported.All ligands and metal complexes were fully characterised, including crystal structures of some species determined by X-ray diffraction on single crystals. This allowed characterising the very different conformations of the macrocycles which could be induced by different substituents or by metal complexation.The strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 43 publications
2
47
1
Order By: Relevance
“…As previously reported for copper(I) complexes, [13] the effect of the metal complexation to the ligand was clearly disclosed by 1 H and 13 C NMR spectroscopy. The partial desymmetrization of the ligand backbone is more evident in the complexes with a pendant naphthyl group on the amine nitrogen (2c-e).…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…As previously reported for copper(I) complexes, [13] the effect of the metal complexation to the ligand was clearly disclosed by 1 H and 13 C NMR spectroscopy. The partial desymmetrization of the ligand backbone is more evident in the complexes with a pendant naphthyl group on the amine nitrogen (2c-e).…”
Section: Resultssupporting
confidence: 53%
“…We evaluated the effect of the counterion on the NMR spectra of silver complexes 2, choosing 2a 1-3 as case studies and, as expected, we observed the same signals in the 1 H, 13 C, and 15 N NMR spectra without any dependence on the coordinating features of the counterion. These complexes showed an apparent Cs symmetry of the structure in solution, with two signals for each couple of equivalent methylene groups.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations